Promotion of Hair Regrowth in Androgenetic Alopecia with Supplemented Erzhi Wan: Exploring Its Mechanism Using Network Pharmacology and Molecular Docking - Ji C; Ma J; Feng C; Zhu H; Gao Y; Huang J; Shen H; Wei Y (Dove Medical Press, 2023)
Chen Ji,1 Jun Ma,2 Chengcheng Feng,1 Hongliu Zhu,3 Yanwei Gao,1 Jun Huang,1 Hui Shen,1 Yuegang Wei4 1Department of Dermatology, Zhangjiagang TCM Hospital Affiliated to Nanjing University of Chinese Medicine, Suzhou, People's Republic of China; 2Department of Dermatology, the Affiliated Zhangjiagang Hospital of Soochow University, Suzhou, People's Republic of China; 3Department of Dermatology, Jiangyin Hospital of Traditional Chinese Medicine, Wuxi, People's Republic of China; 4First College of Clinical Medicine, Nanjing University of Chinese Medicine, Nanjing, People's Republic of ChinaCorrespondence: Hui Shen, Department of Dermatology, Zhangjiagang TCM Hospital Affiliated to Nanjing University of Chinese Medicine, 4 Kangle Street, Suzhou, Jiangsu Province, 215600, People's Republic of China, Email zjgzy046@njucm.edu.cn Yuegang Wei, First College of Clinical Medicine, Nanjing University of Chinese Medicine, 138 Xianlin Road, Nanjing, Jiangsu Province, 210023, People's Republic of China, Email weiyuegang@163.comPurpose: Supplemented Erzhi Wan (SEZW) is a Traditional Chinese Medicine commonly used in the treatment of androgenetic alopecia (AGA). This study aims to verify the effectiveness of SEZW for the treatment of AGA in mice and explore the potential molecular mechanisms underlying its function using network pharmacology and molecular docking.Methods: Forty mice were divided into five groups: Control, AGA-model, AGA-Positive, SEZW Low Dose, and SEZW High Dose. Hair regrowth in mice was evaluated by scoring hair on days 0, 14, and 28 post-treatment and weighing mouse hair on day 28 post-treatment. The targets of the active compounds of SEZW were obtained using the Traditional Chinese Medicine Database. AGA-related targets were downloaded from five databases. Then, the overlapping genes were identified. A protein-protein interaction network was constructed using the STRING database. Hub targets were determined through analysis. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses were performed. Finally, molecular docking of active compounds and hub targets was performed.Results: Hair regrowth in mice in the SEZW treatment groups was significantly enhanced relative to that in the AGA-model mice. A total of 59 potential drug-disease targets were identified. Based on the GO/KEGG analysis results, oxidative stress and gland development were identified as potential mechanisms of action of SEZW in AGA treatment. The PI3K-Akt and AGE-RAGE signaling pathways and seven hub targets were identified as the potential underlying mechanism of SEZW function. Molecular docking results showed that the most active SEZW compounds bind stably to several of the candidate disease targets.Conclusion: SEZW is effective in the treatment of AGA in a mouse model. Combined with network pharmacological analysis, the potential mechanisms, signaling pathways, and hub targets of SEZW in the treatment of AGA were identified, providing new ideas for further studies.Keywords: Chinese herbal formulas, hair loss, hair regeneration, mechanism prediction